Statistical and Experimental Investigation of Hardened AISI H11 Steel in CNC Turning with Alternative Measurement Methods - Emrah Şahin; İsmail Esen (Advances in Materials Science and Engineering)
In recent years, hard turning, an alternative to grinding, which provides low cost and good surface quality, has become an attractive method to the manufacturers. In this experimental study, AISI H11 hot work tool steel that has been hardened up to 50 HRC was subjected to hard turning tests with coated carbide tooling. The analyses were carried out by applying response surface methodology with the analysis of variance method. A total of 27 experiments were modeled utilizing 33 full factorial design and were carried out using a CNC lathe. The effects of the cutting parameters on surface roughness, energy consumption, electric current value, and sound intensity level were investigated. Optimum cutting parameters and levels were determined according to these optimum values. The relationship between cutting parameters and output variables was analyzed with two-dimensional and three-dimensional graphics. The results show that while the most effective parameter on the surface roughness was the feed rate (88.62%), the most effective parameter on the sound intensity level was the cutting speed (44.92%). In addition, the cutting depth was the most effective parameter on both electric current (52.20%) and energy consumption (46.15%). Finally, regression coefficients were determined as a mathematical model, and it was observed that this estimated model gave results that were very similar to those achieved with real experiment (correlation values: 97.64% for surface roughness, 98.72% for energy consumption, 97.22% for electric current value, and 91.38% for sound intensity level).